Uterine smooth muscle tumors of uncertain malignant potential and atypical leiomyoma: A morphological study of these grey zones with clinical correlation - Kedar K Deodhar; Pankaj Goyal; Bharat Rekhi; Santosh Menon; Amita Maheshwari; R Kerkar; H B Tongaonkar (Wolters Kluwer Medknow Publications, 2011)
Objectives: To study the histological features in uterine STUMP, and atypical leiomyomas (AL), and to correlate with clinical outcome. Materials and Methods: From January 2004 to August 2010, a total of 21 cases were retrieved from records, labeled as STUMP(7), AL (5), AL with low risk of recurrence (2), smooth muscle tumor of low malignant potential (STLMP) (2), and symplastic leiomyoma (5). The slides were reviewed for coagulative tumor cell necrosis (CTCN), hyaline necrosis/ infarction type necrosis, presence and degree of cytological atypia, mitotic activity, epithelioid morphology and myxoid features. The other characteristics (such as size, circumscription, individual tumor cell necrosis), were noted, wherever available. Results: The mean age was 45 years (median 46; range 24-67 yrs). CTCN was seen in 2 cases on examination of additional material; wherein a revised diagnosis of leiomyosarcoma had been given. Infarction type necrosis and individual cell necrosis was seen in 2 and 3 cases, respectively. Mitoses were less than 5/10hpf in all the cases. One of the tumours labeled as STUMP also had concurrent endometrial adenocarcinoma. Follow up: Follow-up was available in 11 cases (52.3%). One patient had died. (cause not known). In 10 patients, the follow-up ranged from 4 to 56 months (mean 20.9 months; median 15 months) nine patients were alive and well. One patient (labeled STLMP) had metastatic liver disease 3 yrs after the primary surgery, at the last follow-up. Conclusions: 1) There is an overlap in using the terminologies as STUMP, AL, AL with low risk of recurrence, AL with low malignant potential. A designation of STUMP does convey a category of borderline malignancy to the gynecological surgeons. Most behave in a benign fashion and follow-up without adjuvant therapy is currently recommended. Critical evaluation of coagulative tumor necrosis is essential. Follow-up remains a challenge in our setting.